Risk identification for msxi mutation in non-syndromic cleft lip and palate deformities for the formulation of prevention stra tegtes. - Sulaiman, Wan Azman Wan; Halim, Ahmad Sukari; lsa, Mohd Nizam (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
Orofaciai clefts are congenital structural anomalies of the lip and/or palate that affect between I in 2000 and I in 500 live births worldwide. In Kelantan, it affect I in 600 live births. Their frequent occurrence as well as their extensive psychological, surgical, speech and dental involvement emphasize the importance of understanding the underlying causes. The etiology is complex, including multiple genetic and environmental factors. They can occur as one component of multiple congenital anomaly syndromes or as non-syndromic forms. The non-syndromic forms are more common and are likely due to secondary gene-environment interactions. Recent advances in both molecular and quantitative approaches have begun to identify the genes responsible for the rare syndromic and the more common and complex non-syndromic variants. From January, 1999 until December, 2002, 102 non-syndromic cleft lip and/or palate patients and parents have been studied in Reconstructive Sciences Unit, Universiti Sains Malaysia. All the studied patients have been interviewed to detect the common environmental factors that may contribute to the occurrence of the clefts deformity. From 102 patients included into the study, 41 venous blood samples (patient, father and mother) have been studied for MSX I mutation. MSX I mutation shows a significant contribution to the occurrence of the cleft group compare to the non-cleft control group (P<O.OOO I). Parents MSX I mutation shows a significant contribution to the mutation of the MSX I gene in the cleft patient (P~O.O II) predominantly paternal contribution (P~O.OO I). There is a highly significant possibility for the cleft child to inherit the mutation of the MSXI gene if both parents has the mutation, odd ratio 10.5 at P~0.007. There is no significant contribution of the environmental factors to the mutation of the MSX I gene, but there is a significant contribution of the paternal cigarette smoking to the incidence of clefts in general (P<O.OOO I) in I 02 samples compared to I 00 controls.